A role for translational regulation by S6 kinase and a downstream target in inflammatory pain. (12th September 2021) - de la Peña, June Bryan; Kunder, Nikesh; Lou, Tzu‐Fang; Chase, Rebecca; Stanowick, Alexander; Barragan‐Iglesias, Paulino; Pancrazio, Joseph J.; Campbell, Zachary T.
Abstract : Background and Purpose: Translational controls pervade neurobiology. Nociceptors play an integral role in the detection and propagation of pain signals. Nociceptors can undergo persistent changes in their intrinsic excitability. Pharmacological disruption of nascent protein synthesis diminishes acute and chronic forms of pain‐associated behaviours. However, the targets of translational controls that facilitate plasticity in nociceptors are unclear. Experimental Approach: We used ribosome profiling to probe the translational landscape in dorsal root ganglion (DRG) neurons from male Swiss‐Webster mice, after treatment with nerve growth factor and IL‐6. Expression dynamics of c‐Fos were followed with immunoblotting and immunohistochemistry. The involvement of ribosomal protein S6 kinase 1 (S6K1), a downstream component of mTOR signalling, in the control of c‐Fos levels was assessed with low MW inhibitors of S6K1 (DG2) or c‐Fos (T‐5224), studying their effects on nociceptor activity in vitro using multielectrode arrays (MEAs) and pain behaviour in vivo in Swiss‐Webster mice using the hyperalgesic priming model. Key Results: c‐Fos was expressed in sensory neurons. Inflammatory mediators that promote pain in both humans and rodents promote c‐Fos translation. The mTOR effector S6K1 is essential for c‐Fos biosynthesis. Inhibition of S6K1 or c‐Fos with low MW compounds diminished mechanical and thermal hypersensitivity in response to inflammatory cues. Additionally, both inhibitors reduced evoked nociceptor activity. Conclusion and implications: Our data show a novel role of S6K1 in modulating the rapid response to inflammatory mediators, with c‐Fos being one key downstream target. Targeting the S6 kinase pathway or c‐Fos is an exciting new avenue for pain‐modulating compounds.